Kultur In Vitro Pisang Cavendish (Musa acuminata L.) Pada Media Dengan Konsentrasi Berbeda Ekstrak Jambu Batu Dan Benzyl Amino Purine - Adam Saepudin; Amir Amilin; Undang Undang; Tini Sudartini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
In vitro culture requires suitable media, the addition of BAP as a cytokinin is considered to accelerate the growth of Cavendish bananas. Constraints of browning in explants are also often found in the growth of banana explants. The addition of guava extract as an organic antioxidant and BAP is expected to suppress browning and improve the growth of Cavendish banana explants in vitro. The study was aimed to obtain the best concentration of guava extract (Psidium guajava) and Benzyl Amino Purine for the growth of Cavendish banana (Musa acuminata) explants in vitro. This study used a completely randomized design (CRD) with a factorial pattern of 4 x 3 with 4 replications. Treatment of guava extract added to the media (0 g/l, 1 g/l, 2 g/l, 3 g/l) and BAP (3 ppm, 6 ppm, 9 ppm). The data were analyzed using variance with the F test and continued with Duncan's Multiple Distance Test with 5% significance level. The results showed that the best result for the number of shoots were in the treatment of 1 g/l guava extract + BAP 3 ppm. In the number of leaves and high shoots the best result were in the treatment of 0 g/l guava extract + BAP 6 ppm